2011
DOI: 10.3109/17538157.2010.520418
|View full text |Cite
|
Sign up to set email alerts
|

Web vulnerability study of online pharmacy sites

Abstract: Background. Consumers are increasingly using online pharmacies, but these sites may not provide an adequate level of security with the consumers' personal data. There is a gap in this research addressing the problems of security vulnerabilities in this industry.Objectives. The objective is to identify the level of web application security vulnerabilities in online pharmacies and the common types of flaws, thus expanding on prior studies.Technical, managerial and legal recommendations on how to mitigate securit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 7 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…The works were published between 1999 [57,61,66] and 2011 [78], as shown in Figure 2, which displays the articles described in this section by year of publication and number of online pharmacies in the study sample. Less than half of the studies analyzed had more than 50 online pharmacies in their samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The works were published between 1999 [57,61,66] and 2011 [78], as shown in Figure 2, which displays the articles described in this section by year of publication and number of online pharmacies in the study sample. Less than half of the studies analyzed had more than 50 online pharmacies in their samples.…”
Section: Resultsmentioning
confidence: 99%
“…A special study was performed by Kuzma [78] about the Web vulnerability of a random sample of 60 online pharmacies. She chose as her testing tool the N-Stalker Web Application Security Scanner 2009 Free Edition 7.0, which showed that a majority of worldwide online pharmacies do not provide adequate protection for their consumers, especially in cross-site scripting.…”
Section: Resultsmentioning
confidence: 99%
“…This study did not investigate the ability to purchase controlled substances or drugs for intentional misuse, review the many risks associated with self-prescribing, or review the unique risks associated with international pharmacies such as the potential for confusion of some foreign brand names (FDA, 2006). Technical vulnerabilities previously noted on online pharmacy websites were not assessed (Kuzma, 2011). The growth of online pharmacies and associated problems is an international phenomenon (Orizio et al, 2011;Venhuis et al, 2014), but this study focused only on Internet searches initiated from the US.…”
Section: Limitationsmentioning
confidence: 99%
“…Many sites do not secure customers’ information, post-purchase emails often contain unencrypted links to customer information and online transactions are inadequately protected. 17 Such site vulnerabilities can lead to consumer fraud and inadequate data protection. Moreover, cybercrime related to the COVID-19 pandemic is reported to be extremely dynamic and growing, including online sales of bogus cures, counterfeit test kits and non-delivery scams.…”
Section: Risks To Consumersmentioning
confidence: 99%